Dispositional and situational factors as determinants of food eating behaviour among sedentary and blue-collar workers in Nigeria’s premier teaching hospital (2011)
This cross sectional survey investigated the rate of dispositional (self-efficacy and self-esteem), and situational factors (distractibility and perceived food variety) as determinants of food eating behavior (FEB). Hospital employees (N500) in Nigeria’s premier teaching Hospital participated. Results showed that self-efficacy and self-esteem jointly predicted cognitive restraint dimension of FEB (F(2,499) = 26.00; R2= 0.10; p<.05). dispositional variables jointly predicted uncontrolled eating (F(2,499)=17.41; R2= 0.07; p<.05), emotional eating (F(2,499) = 28.58; R2= 0.10; p<.05), and cognitive restraint (F(2,499) = 35.60; R2=0.13; p<.05) dimensions of FEB. Age (x2= 64.81; df=1; p<.05), and marital status (x2=32.74; df=4; p<.05) were associated with FEB. Therefore, dispositional and situational variables are predictors of FEB as evidenced in previous literatures. The need for primary prevention, and assertiveness to reduce distractibility and eating disorders was highlighted towards maintaining health and efficiency at work is recommended.